Strategi Mengajar Calon Guru yang Mendapat Pendampingan - Cut Morina Zubainur; Dazrullisa Dazrullisa; Marwan Marwan (Universitas Syiah Kuala, 2017)
Abstract. Pedagogical Content Knowledge (PCK) of teachers is an important aspect of professional teachers. PCK teacher originally developed through a process of education at the Institute of Education of Teaching. In addition to theoretical study, during LPTK prospective teachers are also trained through the Training Field Experience (PPL) to gain concrete experience. Assistance for implementing PPL expected to increase PCK prospective teachers. It is for prospective teachers menjembatanikesenjangan understanding of the theory gained with experience gained. The purpose of research is to analyze the strategies of teaching prospective teachers who get assistance and determine the students' understanding is based on the strategy undertaken by prospective teachers. Subjects were a student of Mathematics Education who are conducting PPL and students in the first semester of the academic year 2015/2016 in SMPN 1 Banda Aceh. Data strategy to teach prospective teachers collected through observation of learning activities and interviews of prospective teachers and tests. Data were analyzed based on indicators PCK through the description of the implementation of learning activities prospective teachers. The result showed that the strategy of teaching prospective teachers who receive assistance are already using learning strategy and approach to scientific, it is in choosing the right strategy, the right to choose the context, effective in using time allocation, has designed activities that are appropriate to present the concept of algebra, linking concepts algebra with everyday life in instruction and implementing the learning process in accordance with the design of learning activities. Student understanding based teaching strategies prospective teachers who received student assistance is easy to understand the material and can solve problems that relate to the material.